2023
DOI: 10.3390/biology12030337
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Aortic Syndromes on Non-Contrast CT Images with Radiomics-Based Machine Learning

Abstract: We aimed to detect acute aortic syndromes (AAS) on non-contrast computed tomography (NCCT) images using a radiomics-based machine learning model. A total of 325 patients who underwent aortic CT angiography (CTA) were enrolled retrospectively from 2 medical centers in China to form the internal cohort (230 patients, 60 patients with AAS) and the external testing cohort (95 patients with AAS). The internal cohort was divided into the training cohort (n = 135), validation cohort (n = 49), and internal testing coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“… 57 Ma et al evaluated the potential value of radiomics features obtained from non-contrast computed tomography (NCCT) to detect acute aortic syndrome (AAS) images; they found nine radiomic features, which also included wavelet LLH mean feature, and SVM algorithm showed best performance 0.997 (95% CI, 0.992–1). 58 Furthermore, our findings were consistent with the study conducted by Wang et al, where they also identified several important features, including small dependence low gray-level emphasis, that can be utilized to predict the pretreatment CD8+ T-cell infiltration status in primary head and neck squamous cell carcinoma. 59 Ren et al conducted a study which showed that multimodal radiomics can distinguish between true tumor recurrence (TuR) and treatment-related effects (TrE) in glioma patients with high accuracy (AUC: 0.965 ± 0.069).…”
Section: Discussionsupporting
confidence: 91%
“… 57 Ma et al evaluated the potential value of radiomics features obtained from non-contrast computed tomography (NCCT) to detect acute aortic syndrome (AAS) images; they found nine radiomic features, which also included wavelet LLH mean feature, and SVM algorithm showed best performance 0.997 (95% CI, 0.992–1). 58 Furthermore, our findings were consistent with the study conducted by Wang et al, where they also identified several important features, including small dependence low gray-level emphasis, that can be utilized to predict the pretreatment CD8+ T-cell infiltration status in primary head and neck squamous cell carcinoma. 59 Ren et al conducted a study which showed that multimodal radiomics can distinguish between true tumor recurrence (TuR) and treatment-related effects (TrE) in glioma patients with high accuracy (AUC: 0.965 ± 0.069).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in future research, more advanced automatic annotation methods can be considered to reduce the time and cost of data annotation and ensure the quality of data. Secondly, unlike deep learning, due to the limited amount of data, the classification model used in this paper does not require GPU support [15], so the model can be trained and applied in a central processing unit (CPU) environment. This advantage makes the algorithm easier to implement and promote, and reduces the implementation cost, so it is more suitable for practical applications in the medical field.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic features exhibit high correlation with each other or irrelevant to stenosis detection. Both can lead to over-fit of the model [12]. Therefore, the necessity for feature selection and reduction becomes apparent.…”
Section: Radiomics Feature Reductionmentioning
confidence: 99%